PERAN PEMERINTAH DAERAH KABUPATEN TEBO DALAM PENGAKUAN DAN PERLINDUNGAN MASYARAKAT SUKU ANAK DALAM TAHUN 2020 – 2022 - Sepmawati, Rema; Yusri, Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The Anak Dalam Tribe is a minority group socially, politically and developmentally, which makes the Anak Dalam Tribe need to get protection, recognition and empowerment from the Regional Government, the Regional Government needs to make policies to protect the Anak Dalam Tribe, the Anak Dalam Tribe needs special treatment based on policies that made by the regional government so that it supports the lives they live, as well as avoiding violations of the rights of the Anak Dalam Tribe community. The aim of this research is to analyze the role of the Tebo district local government in protecting and recognizing the Anak Dalam tribal community in 2020 - 2022. The method in this research uses a qualitative approach. The theory used is the Government Role theory according to Ryaas Rasyid (1996) which includes: 1) Facilitator 2) Regulator 3) Dynamisator. The results of this research based on Ryass Rasyid's theory can be seen in the Facilitator indicator, the role of local government has been carried out by providing assistance facilities to tribal communities and providing facilities for socializing. from the Regulator indicators, the role of local government is only to set SK. In the Dynamics indicator, it can be seen that the role of regional government has been to carry out socialization and assistance activities for tribal communities, accompanied by social services, health services and other organizations. The performance of the Tebo Regency regional government is still not optimal, which can be seen from the regulator's indicators. Keywords : Role, Local Government, Suku Anak Dalam